Utilization of Local Wisdom Videos for Enrichment of Students' Poetry Interpretation in the Form of Essays - Shalawati Shalawati; Teguh Trianton; Dian Syahfitri (Prodi PAI STIT Sunan Giri Bima, 2025)
The use of videos based on local wisdom in literature learning is an innovative approach that can enrich the interpretation of poetry and improve students' essay writing skills. The purpose of this study is to describe the use of local wisdom videos to enrich the interpretation of poetry in the form of essays by 10th grade students at SMK Negeri 1 Simpang Kiri Kota Subulussalam. This study employs a qualitative approach using a descriptive method. Informants were selected purposively according to research needs. Data collection was conducted through in-depth interviews, observations, and document analysis. Data analysis followed the qualitative analysis stages outlined by Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of local wisdom videos, such as the Peusijuk tradition, kenduri, and gotong royong, can shape more contextual, connotative, and symbolic interpretations of poetry. Students demonstrated improved abstract and reflective thinking skills and greater confidence in writing essays. Student responses were very positive because the visual media presented were relevant to their lives, making learning more active, personal, and meaningful. However, there were some challenges, such as technical limitations, differing cultural backgrounds, and low literary literacy. Despite this, teacher support, a flexible curriculum, and the integration of local values were key factors contributing to the success of this strategy. This approach strengthens understanding of poetry and fosters a deeper appreciation of literature through authentic learning experiences.